2008
DOI: 10.1634/stemcells.2007-1081
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive MicroRNA Profiling Reveals a Unique Human Embryonic Stem Cell Signature Dominated by a Single Seed Sequence

Abstract: Embryonic stem cells are unique among cultured cells in their ability to self-renew and differentiate into a wide diversity of cell types, suggesting that a specific molecular control network underlies these features. Human embryonic stem cells (hESCs) are known to have distinct mRNA expression, global DNA methylation, and chromatin profiles, but the involvement of high-level regulators, such as microRNAs (miRNA), in the hESC-specific molecular network is poorly understood. We report that global miRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
188
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(205 citation statements)
references
References 80 publications
16
188
0
1
Order By: Relevance
“…The pluripotency-associated miR-302 cluster (miR-302a, -302b, -302c, -302d, and -367) declined over the differentiation time course (Fig. 3B), as expected [39,40]. Although the levels of the miRNAs never returned to baseline, even at 120 days, such residual miR-302 expression has been observed in other differentiation experiments [39,41,42].…”
Section: Mirna Profiling During Hipsc Differentiationsupporting
confidence: 72%
See 1 more Smart Citation
“…The pluripotency-associated miR-302 cluster (miR-302a, -302b, -302c, -302d, and -367) declined over the differentiation time course (Fig. 3B), as expected [39,40]. Although the levels of the miRNAs never returned to baseline, even at 120 days, such residual miR-302 expression has been observed in other differentiation experiments [39,41,42].…”
Section: Mirna Profiling During Hipsc Differentiationsupporting
confidence: 72%
“…3B), as expected [39,40]. Although the levels of the miRNAs never returned to baseline, even at 120 days, such residual miR-302 expression has been observed in other differentiation experiments [39,41,42]. The let-7 family of miRNAs, which reinforce the commitment to differentiation [43], also exhibited the expected expression pattern with the levels increasing during differentiation (Supplementary Fig.…”
Section: Mirna Profiling During Hipsc Differentiationsupporting
confidence: 59%
“…The miRNA profile showed the hESC-specific expression signature (Figure 2(b)), consistent with previous studies (Suh et al 2004;Laurent et al 2008). First, miRNAs bearing the ESC-specific seed (AAGUGCU), which originated predominantly from the miR-302-367 cluster and to a much lesser degree, from the miR-371-373 cluster, were dominant.…”
Section: Ago2-bound Microrna Profiling In Human Embryonic Stem Cellssupporting
confidence: 89%
“…We found that inhibition of epigenetic silencing caused upregulation of two miR clusters located on chromosome 19: the C19MC (ch19 miR cluster) and the miR-371-373 cluster, both associated with human embryonic stem cells. 14 We subsequently focused on one representative miR from each cluster: miR-512-5p (miR-512) and miR-373, respectively. We report that both miRs can exert negative effects on lung cancer cells, including induction of apoptosis and inhibition of cell migration.…”
mentioning
confidence: 99%